IMPLEMENTATION OF MERDEKA CURRICULUM BY PHYSICS TEACHER IN SMAN 1 PANCUR BATU - Jawak, Noni Prince; Siregar, Alkhafi Maas (UNIVERSITAS NEGERI MEDAN, 2024)
The aim of the research is to discover how teachers participate in physics learning using the Merdeka Curriculum through Science Process Skill of X2 students. The research is descriptive quantitative research method. Based on the results, the assessment concluded that student participation in the learning process at SMA Negeri 1 Pancur Batu is 45.7%, which is considered good. However, the student effective learning percentage at SMA Negeri 1 Pancur Batu is enough, at 37.1%. The indicator of no students being unable to comprehend at SMA Negeri 1 Pancur Batu is 45.7%, which is considered very good. Overall, the Merdeka Curriculum implementation indicators from the evaluation of students in the good category are 57.1%. According to the observation form results, 24 statement items of the 30 are accomplished, with 6 statement items not complying, indicating that the physics teacher's implementation of the Merdeka Curriculum in the X2 class is very good. For Science Process Skills of students X2 are categorized as good with a percentage of 67.71%. So, it can be defined that the Physics Teacher's implementation of the Merdeka Curriculum to students in class X2 using a Science Process Skills method is considered good.